Image encryption scheme based on a controlled zigzag transform and bit-level encryption under the quantum walk - Zhang, Tian; Wang, Shumei (Frontiers in Physics, 2023)
With the rapid development of science and technology and network technology, the study of information security has become a hot spot, and image encryption has potential value in this regard. In this paper, an image encryption scheme based on controlled zigzag transform and bit-level encryption in the quantum walk environment is proposed. Firstly, the parameters of the alternating quantum walk are obtained by using the sha256 method, and the probability matrix of the quantum distribution on the two-dimensional lattice is obtained by multiple walk measurements; secondly, the spatial dislocation and bit-level dislocation of the image are realized by performing controlled zigzag dislocation and 3-dimensional tesseract-like rotational dislocation on the color image; finally, after preprocessing the probability matrix of the quantum distribution, the matrix is compared with the dislocated image by bit-by-bit Finally, after preprocessing the probability matrix of quantum distribution, the matrix and the scrambled image are subjected to bit-by-bit dissimilarity to achieve the encryption protection of image information. The effectiveness of the encryption scheme is verified by simulation experiments, and the scheme has a great encryption effect. Compared with other encryption schemes, this scheme has better key sensitivity and dislocation effect, which provides a new approach to the field of image quantum encryption.